Concordance between botanical groups and genetic diversity in peanut - Machado, Ingrid; Silva, Fernanda Helena; Matos, Renata; Silva, Tamiris; DoVale, Júlio (Revista Ciência Agronômica, 2017)
The aims of this study were to characterize peanut accessions of germplasm collection of the CCA/UFC and check consistency between the pre-existing botanical groups to estimates of genetic diversity. For this were conducted a trial with 43 accessions of peanut in a randomized block design with three replications. To characterization were used 21 morphological descriptors, where revealed large genetic variation. The mass hundred grains trait showed the main discriminating factors, with relative percentage of 22.1%. The cluster obtained with the linkage complete method, it was possible to view the dendrogram the formation of seven groups based on the Mahalanobis distance. By principal components analysis was identified phenotypic diversity among genotypes. The first three components explained 81% of the total variation. Subsequently, built a three-dimensional scatter chart for access of visualization, eight groups being formed. There was medium magnitude of agreement between the botanical groups and genetic diversity, both by the dendrogram and graphic dispersion proving the dissimilarity between genotypes of different botanic groups. Therefore, crossings between group access botanical Spanish or Valencia with those belonging to the Virginia group should generate segregating populations with high genetic potential.